a morphological Study of the Small Intestine in the Geese (Anser anser). - radwan, zeena; Taha Katta Khalaf (University of Thi-Qar Journal of agricultural research, 2023)
This study aimed to identify morphological of the small intestine in adult geese. Six healthy geese were bought from the Baghdad local market, their age from (2- 5) years, and weight from (1.5 - 2.5) kg. All geese were euthanized and their coelomic cavity was dissected to determine the placement of the digestive organs, including their relative shapes. The coelomic cavity was dissected from the thoracic intake to the vent orifice. Gross descriptions and measurements of the small intestine were taken, including its length, weight, diameter, relative length, and relative weight according to the morphological investigation. Our results showed that the small intestine is made up of three segments (duodenum, jejunum, and ileum), The duodenum forms a U-shaped tube that occupied the pancreas, jejunum has (5) fluxes. Mickel’s diverticulum appeared as a small bunch separating the jejunum from the illum. Illum was shorter than the rest of the small intestine.